Unconjugated hyperbilirubinaemia in achalasia. Issue 2 (February 1974) - Fevery, J.; Heirwegh, K. P. M.; De Groote, J.
Abstract : Moderate unconjugated hyperbilirubinaemia decreasing after pneumatic dilatation of the gastrooesophageal sphincter, so permitting a normal amount of food to be taken was observed in two patients with achalasia. Liver biopsy was performed, and hepatic digitonin-activated bilirubin UDP-glucuronyltransferase activity was decreased in both, as is usually found in patients with Gilbert's syndrome. In the patients examined the slight and variable hyperbilirubinaemia associated with Gilbert's syndrome seemed thus to have been aggravated because of the decreased food intake due to achalasia. This situation may be compared to the jaundice sometimes found in neonates with pyloric stenosis or other types of obstruction of the upper gastrointestinal tract. Observations in rats and man favour a complex mechanism for fasting-induced hyperbilirubinaemia.